A model study of low-frequency noise exposure indoors due to road traffic. Issue 1 (March 2023) - Forssén, Jens; Zachos, Georgios; Rosas Perez, Carmen; Kropp, Wolfgang
Indoor low-frequency noise levels due to road traffic has been modelled for facade examples consisting of a lightweight steel facade, a concrete facade and two types of windows. Possible audibility of heavy vehicles passing by has been investigated as well as the dependence of the exposure level on driving speed and distance to road. The results show that pass-by events may be audible at low frequencies for cases complying with building standards and noise guideline values exemplified by Swedish regulation. Moreover, the A-weighted levels may be dominated by low frequency noise, and the frequency of occurrence of pass-by traffic noise events may be sufficiently high to create disturbance for typical traffic situations. Furthermore, it is shown that the contribution of pass-by events to the equivalent level indoors may increase when the driving speed is lowered.